Digital Public Engagement through Social Media in Archaeology – How to Choose. Issue 1 (3rd March 2016) - Rocks-Macqueen, Doug
Since the creation of the World Wide Web in the 1990s we have seen exponential growth in digital engagement platforms. Archaeologists are now faced with a wide range of digital engagement tools to choose from, especially in the area of social media. However, it is not possible to use all the available social media tools and many people are at a loss as to which one is the 'best.' This paper investigates what criteria one should use to evaluate the different social media options. This is done through a series of examples from the author's personal experience.